(untitled) (The NOUN Journal of Agricultural Research and Development (NJARD), 2025)
Field experiment was conducted during the 2024 rainy season at the Teaching and Research Farm, Faculty of Agriculture, Bayero University Kano (BUK), and the National Horticultural Research Institute (NIHORT), Bagauda, to assess the effect of charcoal on the growth and yield of sorghum. Four charcoal application rates (0, 5, 10, and 15 t/ha) were arranged in a randomized complete block design with three replications. Results of the study indicated that charcoal application significantly (p < 0.05) influenced plant height, panicle weight, 1000 grain weight, grain yield, and biomass weight. The 10 t/ha treatment consistently produced the highest values for panicle weight (2656 kg/ha and 2958.96 kg/ha), biomass (5391 kg/ha and 5807.41 kg/ha), and grain yield (2244.44 kg/ha and 2686 kg/ha) at both locations. Grain yield showed a strong positive correlation with plant height, panicle weight, panicle length, and biomass. The findings suggest that charcoal enhances soil productivity and sorghum performance, with 10 t/ha identified as the optimal rate under the study conditions.